Developing Public-Speaking Agency Through Muhadharah: An Exploratory Study of Female Students in an Indonesian Islamic Boarding School - Era Sapitri; Rina Juliana (Women, Education, and Social Welfare, 2026)
This study aims to explore how Muhadharah, a structured religious public-speaking program, develops public-speaking agency among female students in an Indonesian Islamic boarding school. Using a qualitative institutional case-study design, data were drawn from three role-specific semi-structured interviews with the boarding-school leader, a female Muhadharah advisor, and one participating student. Interview data were analyzed through reflexive thematic analysis and role-based comparison. The findings reveal an institutional performance cycle consisting of protected weekly scheduling, rotating communicative roles, script preparation, peer-mentor support, repeated rehearsal, live delivery, collective feedback, and recognition. The student described a gradual transition from fear and embarrassment toward stronger confidence, clearer delivery, improved intonation, and greater responsibility. Program continuity was constrained by memorization demands, anxiety, limited time, competing activities, weather, and power interruptions, but was supported through group rotation, mentor assistance, alternative venues, portable lighting, and reward-based reinforcement. The study positions Muhadharah as a gender-responsive support system rather than merely a speech-training activity. It recommends a staged progression from full scripts to outline-based speaking, rubric-guided formative feedback, and protected low-stakes performance opportunities.